Tensions in Islamic Economics - Edward Mariyani (Faculty of Economics and Business, University of Pasundan, 2013)
The discipline of modern Islamic economics is currently torn in opposing directions by different visions of what its nature should be. On one side, it is argued that modern Islamic economics is too heavily influenced by secular economic theory. On the other side, it is argued that an overreliance on theologically-informed ideals would render Islamic economics unduly unrealistic. This paper explores the two competing criticisms of modern Islamic economics, illustrating how the conflict is played out in the area of Islamic banking. A case is tentatively made for greater pluralism in modern Islamic economics as a means of moving the discipline forward.